1998
DOI: 10.1002/(sici)1097-0061(199802)14:3<225::aid-yea215>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

The Saccharomyces cerevisiae TGL2 gene encodes a protein with lipolytic activity and can complement an Escherichia coli diacylglycerol kinase disruptant

Abstract: Escherichia coli cells with a disrupted diacylglycerol kinase gene are unable to grow on media containing arbutin due to a lethal accumulation of diacylglycerol. In order to isolate genes from the yeast Saccharomyces cerevisiae involved in diacylglycerol metabolism we complemented an E. coli diacylglycerol kinase disruptant with a yeast genomic library and transformants were selected capable of growing in the presence of arbutin. Using this method, a gene (TGL2) was isolated coding for a protein resembling lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Tgl1 has been proposed to be a triglyceride-specific lipase on the basis of its homology to lipases from humans and rats, but enzymatic activity of Tgl1 against triacylglycerol has never been demonstrated (1). TGL2, on the other hand, was found to prevent lethal accumulation of diacylglycerol (DAG) in a DAG kinase mutant Escherichia coli strain grown on arbutin, an artificial phosphoglycerol acceptor (49). Tgl2p displays sequence homology to Pseudomonas triacylglycerol lipases, and its expression in E. coli confers lipolytic activity against triacylglycerol and DAG with short-chain fatty acids (49).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tgl1 has been proposed to be a triglyceride-specific lipase on the basis of its homology to lipases from humans and rats, but enzymatic activity of Tgl1 against triacylglycerol has never been demonstrated (1). TGL2, on the other hand, was found to prevent lethal accumulation of diacylglycerol (DAG) in a DAG kinase mutant Escherichia coli strain grown on arbutin, an artificial phosphoglycerol acceptor (49). Tgl2p displays sequence homology to Pseudomonas triacylglycerol lipases, and its expression in E. coli confers lipolytic activity against triacylglycerol and DAG with short-chain fatty acids (49).…”
mentioning
confidence: 99%
“…TGL2, on the other hand, was found to prevent lethal accumulation of diacylglycerol (DAG) in a DAG kinase mutant Escherichia coli strain grown on arbutin, an artificial phosphoglycerol acceptor (49). Tgl2p displays sequence homology to Pseudomonas triacylglycerol lipases, and its expression in E. coli confers lipolytic activity against triacylglycerol and DAG with short-chain fatty acids (49). The physiological function of TGL2 in yeast, however, has not been characterized.…”
mentioning
confidence: 99%
“…It would be most interesting to study this gene and its product in more detail, because triacylglycerol lipase(s) of the yeast have not yet been identified at the molecular level. Two other yeast genes possibly involved in triacylglycerol metabolism, namely TGL1 (Abraham et al, 1992) and TGL2 (van Heusden et al, 1998), were recently detected. Both gene products, however, could not be unambiguously identified as triacylglycerol lipases.…”
mentioning
confidence: 99%
“…that the TGL2-like protein might not be essential in yeast and fungi, which is in agreement with previous studies describing the growth ability of the deletion strain of the TGL2 gene on minimal medium (Van Heusden et al, 1998;Ham et al, 2010). However, it has been found that the TGL2 protein is required for the viability of cells treated with antimitotic drugs (Ham et al, 2010).…”
Section: Microbial Lipase Enzymesmentioning
confidence: 99%